Development of Galactose Biosensor Based on Functionalized ZnO Nanorods with Galactose Oxidase. (4th July 2012) - Khun, K.; Ibupoto, Z. H.; Nur, O.; Willander, M.
Abstract : The fabrication of galactose biosensor based on functionalised ZnO nanorods is described. The galactose biosensor was developed by immobilizing galactose oxidase on ZnO nanorods in conjunction with glutaraldehyde as a cross-linker molecule. The IRAS study provided evidence for the interaction of galactose oxidase with the surface of ZnO nanorods. The electromotive force (EMF) response of the galactose biosensor was measured by potentiometric method. We observed that the proposed biosensor has a linear detection range over a concentration range from 10 mM to 200 mM with good sensitivity of89.10 ± 1.23 mV/decade. In addition, the proposed biosensor has shown fast time response of less than 10 s and a good selectivity towards galactose in the presence of common interferents such as ascorbic acid, uric acid, glucose, and magnesium ions. The galactose biosensor based on galactose oxidase immobilized ZnO nanorods has a shelf life more than four weeks.